PERSEPSI GURU DALAM MENINGKATKAN MUTU PENDIDIKAN BERBASIS SISTEM INFORMASI MANAJEMEN DI SEKOLAH DASAR NEGERI 08 BATANG ANAI - Asnita Putri Dewi; Ahmad Sabandi (Jurnal Bahana Manajemen Pendidikan, 2019)
This study aims to obtain information about Teacher's Perception to increase of academic quality based of Management Information Systems at Elementary School 08 Batang Anai which is viewed from aspects: quality and management information system. This type of research is descriptive. The sample in this research were all teachers in SDN 08 Batang Anai, amounting to 11 peoples. Research method is qualitative descriptive. The data that has been collected by obsrvation and interview with the teachers and employee in that school. The result showed that: 1. Teacher's perception in improving the quality of education in SDN 08 Batang Anai is considered weak. The number of those who complained about being unable and lacking in expertise made the quality of education in these schools decline. 2. Teachers' perceptions in using the Management Information System in Schools are also considered weak. Some senior teachers who only rely on school operators make the information system not run smoothly as it should.